Magnified Sediment Export of Small Mountainous Rivers in Taiwan: Chain Reactions from Increased Rainfall Intensity under Global Warming. - Tsung-Yu Lee; Jr-Chuan Huang; Jun-Yi Lee; Shih-Hao Jien; Franz Zehetner; Shuh-Ji Kao (PLoS ONE, 2015)
Fluvial sediment export from small mountainous rivers in Oceania has global biogeochemical significance affecting the turnover rate and export of terrestrial carbon, which might be speeding up at the recognized conditions of increased rainfall intensity. In this study, the historical runoff and sediment export from 16 major rivers in Taiwan are investigated and separated into an early stage (1970-1989) and a recent stage (1990-2010) to illustrate the changes of both runoff and sediment export. The mean daily sediment export from Taiwan Island in the recent stage significantly increased by >80% with subtle increase in daily runoff, indicating more sediment being delivered to the ocean per unit of runoff in the recent stage. The medians of the runoff depth and sediment yield extremes (99.0-99.9 percentiles) among the 16 rivers increased by 6.5%-37% and 62%-94%, respectively, reflecting the disproportionately magnified response of sediment export to the increased runoff. Taiwan is facing increasing event rainfall intensity which has resulted in chain reactions on magnified runoff and sediment export responses. As the globe is warming, rainfall extremes, which are proved to be temperature-dependent, very likely intensify runoff and trigger more sediment associated hazards. Such impacts might occur globally because significant increases of high-intensity precipitation have been observed not only in Taiwan but over most land areas of the globe.